2021
DOI: 10.1016/j.ijid.2020.11.204
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and characteristics of patients hospitalized for Influenza or COVID-19 in Germany

Abstract: Highlights Male sex and old age associated with poor outcome for both diseases. Overall, inhospital mortality is twofold higher for COVID-19 patients. Ventilation time is more than three times longer for COVID-19 than for Influenza. COVID-19 patients discharged after ventilation stayed in hospital twice as long. The proportion of patients with severe outcomes higher for COVID-19 than for Influenza.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
98
3
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(128 citation statements)
references
References 31 publications
23
98
3
4
Order By: Relevance
“…Symptoms of COVID-19 appear very similar to FLU, especially in the early phase of infection, and therefore, FLU represents an optimal comparator for COVID-19. To date, clinical features and outcomes in critically ill patients with FLU and COVID-19 are not widely described [35][36][37][38]. Therefore, in the present study, we contributed to the comparison between FLU and COVID-19 and we found that in critically ill patients requiring ICU admission male sex, age > 65 and higher lymphocytes counts were associated with COVID-19, whereas CKD and COPD were related to FLU, respectively.…”
Section: Discussionmentioning
confidence: 74%
“…Symptoms of COVID-19 appear very similar to FLU, especially in the early phase of infection, and therefore, FLU represents an optimal comparator for COVID-19. To date, clinical features and outcomes in critically ill patients with FLU and COVID-19 are not widely described [35][36][37][38]. Therefore, in the present study, we contributed to the comparison between FLU and COVID-19 and we found that in critically ill patients requiring ICU admission male sex, age > 65 and higher lymphocytes counts were associated with COVID-19, whereas CKD and COPD were related to FLU, respectively.…”
Section: Discussionmentioning
confidence: 74%
“…Six studies initially identified in preprint were subsequently excluded since they had not been peer-reviewed and published by 28 th January 2021; additionally, one study that was initially included based on preprint was subsequently removed since the peer-reviewed version did not meet our study's inclusion criteria. In total, 59 studies [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] were selected for the qualitative synthesis, of which 39[ [23] , [24] , [25] , …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the odd phenomenon of low COPD rates among patients seems unique to COVID-19 ( Table 1 ), as well as SARS and MERS [3] , [4] , [5] , [6] , [7] , [8] . In contrast, the prevalence of COPD and other pulmonary diseases were often higher than other medical comorbidities among patients with influenza or respiratory syncytial virus infections at about 20-40% [9] , [10] , [11] , [12] , [13] , [14] . Deciphering why host susceptible factors vary in response to different respiratory viral infections would also be an area of research interest.…”
Section: Consequences Of the Hypothesismentioning
confidence: 88%
“…Importantly, their causative agents, SARS-CoV-1 and MERS-CoV, also mainly target the alveolar epithelial cells in the lower respiratory tract to cause diseases [82] , [101] , [102] . In contrast, COPD is more prevalent among patients infected with influenza and respiratory syncytial viruses at 20-40% of cases [9] , [10] , [11] , [12] , [13] , [14] , higher than the general population at 10-15% [17] , [18] . Notably, influenza and respiratory syncytial viruses primarily cause upper respiratory tract diseases [103] , [104] , [105] , [106] .…”
Section: Hypothesismentioning
confidence: 91%
See 1 more Smart Citation